DESAIN DAN PEMBANGUNAN SISTEM DAN LAYANAN VIRTUAL PENJUALAN BERBASIS WEBSITE UNTUK TOKO SKINCARE FOUR BEAUTY - Cindy Yulia; Abdul Khaliq (Jurnal Nasional Teknologi Komputer, 2025)
As technology rapidly advances, many business sectors are shifting to digital platforms, including the skincare industry. The aim of this study is to design and develop an effective and efficient website-based sales system for the Four Beauty skincare store. This system is designed to provide convenience for customers shopping online, while also simplifying inventory and transaction management for the store operators. The development approach used for this system is the Agile software development model, supported by technologies such as PHP, HTML, CSS, JavaScript, and MySQL for database management. The outcome of this development is an integrated online store website featuring various functions, such as a product catalog, payment system, and management of transactions and customer data, all of which enhance the overall digital shopping experience for customers.